CONTEMPORARY APPROACHES FOR SELECTING AND EVALUATING ORGANIZATIONAL SOLUTIONS - Pavel Oleynik; Ivan Doroshin; Ruben Kazaryan; Elen Bilonda Tregubova (Journal of Mechanics of Continua and Mathematical Sciences)
The process of selection and evaluation of organizational solutions is considered. Five approaches to the evaluation of organizational solutions used in domestic practice are disclosed, indicating the area of their application. Based on a comparative analysis, the paper provides evidence for the fundamental distinctions between the mathematical and applied methods of selecting optimal solutions. The mathematical process is presented as a search for the best solution to problems and as a process of finding an extremum. The applied process is presented in the form of various indicators and their combinations. The arguments presented suggest that relying on a singular approach and a single metric for evaluating organizational solutions is deemed unfeasible. The paper substantiates the provisions of probability theory and mathematical statistics in the design of transport facilities, organization ofconstruction, and operation of roads. Ensuring the specified reliability of a transport facility requires taking into account probabilistic factors both at the design stage and at the stages of construction and operation of the facility.